INTERNAL DYNAMICS WITHIN HADHRAMI ARABS IN INDONESIA: From Social Hierarchy to Islamic Doctrine (JOURNAL OF INDONESIAN ISLAM, 2017)
This paper examines the current landscape of Hadhrami Arab Community in Indonesia. It aims to understand the internal fissures that affect the cohesion within the community. Some scholars contended that the conflicts taking place within the Hadhrami community are due to the Yemeni traditional stratification and nationalist orientation during colonial era. However, they do not include in their analysis the contemporary state of Hadhramis in Indonesia. This paper focuses on the contemporary era and argues that doctrinal contest and competition for religious authority have dominated the dynamics of conflict within Indonesian Hadhrami community. The paper will touch on the debates on the notion of Shi’ism among the so-called sayyids and Salafism among the followers of Al-Irsyad Al-Islamiyyah. It suggests that it is through these two currents of thought that the Hadhrami community in Indonesia not only exercise their power and authority, but also shape and transform their very identity.